Factors associated with knowledge of the nursing staff at a teaching hospital on blood transfusion - Jordânia Lumênia Tavares; Elizabeth Barichello; Ana Lúcia De Mattia; Maria Helena Barbosa (Universidade de São Paulo, 2015)
AbstractObjective: to determine whether there is an association between knowledge of the nursing professionals about blood transfusion and the variables related to the professional aspects.Method: this is an observational, cross-sectional and quantitative study, carried out at a large general teaching hospital. The sample consisted of 209 nursing professionals, obtained by simple random sampling. For data collection, a checklist was used. In the univariate analysis, descriptive statistics and central trend and dispersion measures were used. In the bivariate analysis, Student's t-Test, analysis of variance and Pearson's correlation were used. To determine the predictors, multiple linear regression was applied. The Institutional Review Board (Opinion number 2434) approved the study.Results: the overall average knowledge score was 52.66%; in the Pre-transfusion Step, it corresponded to 53.38%; in the Transfusion Step 51.25% and, in the Post-transfusion Step, 62.68%. The factors related to knowledge were professional category and received training and/or guidance to accomplish the transfusion process (p<0.01).Conclusion: this study showed the influence of training and guidance on the knowledge and provided a diagnosis to identify the professionals' difficulties regarding the transfusion process.